BEING BOTH "TRANSNATIONAL" AND "NATIONAL & LOCAL" IN HIGHER EDUCATION CONTEXT: ONLINE AND SOCIAL EMOTIONAL LEARNING - Mulyanto, Jaya Dani (Seminar Nasional Ilmu Terapan, 2023)
The world has been facing a massive change in digital technology and its application. Indonesia, as an emerging economy, is not an exception. Recent data show that Indonesia's information and communication technology penetration is unprecedented and will rapidly increase in the coming years. Internet users, for example, are expected to reach almost two hundred seventy million people by 2028. This trend provides many opportunities, including online learning for higher education institutions. The quantity and quality of online learning services are constantly improving, with more human-centred design. Nevertheless, technology generally leaves an unfulfilled gap, as conveyed in human and machine interaction. This non-cognitive dimension is completed and filled with social and emotional learning (SEL). The discussion argues that combining digital technology and SEL application will leverage a learner's horizon and competencies to compete in the 21st-century globalized world. While it can tap the full potential for productive engagement in transnational scope, it also supplies national and local grounding and bounding. Thus, it is aligned with the direction of being global and local (glocal) simultaneously.